When Can Humble Top Executives Retain Middle Managers? The Moderating Role of Top Management Team Faultlines - Ou, Amy Y.; Seo, Jungmin (Jamie); Choi, Dongwon; Hom, Peter W. (Academy of Management Journal, 2017)
Top management in organizations must effectively retain middle managers (MMs)—who are central linking pins in strategy processes—as loss of their human and social capital can threaten strategy implementation. While long envisioning how leaders motivate subordinates to stay, management scholars have largely neglected how teams in which leaders belong (e.g., top management teams [TMT]) constitute an organizational context that moderates their ability to retain subordinates. Building on recent theory and research that a leader’s humility discourages subordinates from voluntarily departing by increasing their job satisfaction, we propose that faultlines in TMTs can exert cross-level effects attenuating how humble executives sustain MMs’ job satisfaction, and how MMs’ job dissatisfaction drives their voluntary turnover. We verify these effects with a multisource, multiphase dataset of 43 TMTs, 313 top executives, and 502 MMs. Our study thus bridges the macro and micro divide to offer a multilevel inquiry into contextual influences on voluntary turnover, identifies a boundary condition for leader humility effects, and clarifies how TMT faultlines represent a contextual constraint on how top executives induce MM subordinates to stay.